The cotton cloth Qur’an binding of the East Coast of the Malay Peninsula / Ros Mahwati Ahmad Zakaria - Ahmad Zakaria, Ros Mahwati (2016)
This study is to analyse the physical criterias of the cotton colth Qur’an binding of the East Coast of the Malay Peninsula. Cotton is a type of textile used as the East Coast Qur’an binding. It is also of good quality that received high demand throughout the world prior to the 20th century. Before the 20 century, the cotton industry reached the Malay world through two routes, firstly via direct trade from India that had taken place prior to the arrival of Western colonization and secondly, through the East India Company, which turned the colonies under its control into revolutionary markets for British industry. A total of 150 Quran manuscript artefacts were used in this study. Each cotton cloth design was analysed and divided into categories such as coloured, striped, patterns with Indian influence and English patterns, based on the motif used. The red covers of Qurans from the East Coast of the Malay Peninsula have been identified to use cotton cloth as the inner cover for manuscripts, which is known as the end paper. The pattern and colour used showcases the taste and exclusivity of the binding of Qurans with red leather covers from the East Coast. It is also one of the defining features of Qurans with red leather covers from the East Coast of the Malay Peninsula.